Water management through land configuration in Bhal region - MALIWAL, M G; DAS, A; RAMANI, V P; BAMBHANIYA, L B (The Indian Journal of Agricultural Sciences, 2013)
A field experiment was conducted during 1989-90 to 1994-95 at Arnej to study the effect of raised and sunken bed system on different cotton (Gossypium hirsutum L.) and pigeonpea [Cajanus cajan (L.) Millsp.] based cropping sequences. The treatment consists of 3 width of bed (3,6 and 9) raised at 30 cm height in main plot and 4 crop sequences in split-plot design, viz cotton-wheat (Triticum aerstivum L. emend Fiori & Paol), cotton-gram (Cicer arietinum L.), pigeonpea-wheat and pigeonpea-gram in sub-plot. Tpe ’G Cot 13’ cotton and ’T 15-15’ pigeonpea were sown on raised bed in rainy season (kharif) and ’GW 1 ’wheat and ’Chaffa’ gram (Cicer arietinum) in sunken bed during winter season (rabi) and 1 supplementary irrigation of 50 mm was given to rabi crops from harvested run-off water in dug farm pond. The results revealed that ’G Cot 13’ cotton to be grown on raised bed (6 or 9 m width raised 30 cm height) in kharif and ’GW 1’ wheat as rabi crop in sunken bed of same width as raised bed with 30 cm depth for Bhal and coastal agroclimatic zone to harvest higher total production and get higher return.